Blood Pressure Changes Following Antihypertensive Medication Reduction, by Drug Class and Dose Chosen for Withdrawal: Exploratory Analysis of Data From the OPTiMISE Trial - Sheppard, James P.; Lown, Mark; Burt, Jenni; Ford, Gary A.; Hobbs, F. D. Richard; Little, Paul; Mant, Jonathan; Payne, Rupert A.; McManus, Richard J.; , On behalf of the OPTiMISE Investigators (Frontiers in Pharmacology, 2021)
Aims: Deprescribing of antihypertensive drugs is recommended for some older patients with polypharmacy, but there is little evidence to inform which drug (or dose) should be withdrawn. This study used data from the OPTiMISE trial to examine whether short-term outcomes of deprescribing vary by drug class and dose of medication withdrawn. Methods: The OPTiMISE trial included patients aged ≥80 years with controlled systolic blood pressure (SBP; <150 mmHg), receiving ≥2 antihypertensive medications. This study compared SBP control, mean change in SBP and frequency of adverse events after 12-weeks in participants stopping one medication vs. usual care, by drug class and equivalent dose withdrawn. Equivalent dose was determined according to the defined daily dose (DDD) of each medication type. Drugs prescribed below the DDD were classed as low dose and those prescribed at ≥DDD were described as higher dose. Outcomes were examined by generalised linear mixed effects models. Results: A total of 569 participants were randomised, aged 85±3 years with controlled blood pressure (mean 130/69mmHg). Within patients prescribed calcium channel blockers, higher dose medications were more commonly selected for withdrawal (90% vs. 10%). In those prescribed beta-blockers, low dose medications were more commonly chosen (87% vs. 13%). Withdrawal of calcium channel blockers was associated with an increase in SBP (5mmHg, 95%CI 0 to 10 mmHg) and reduced SBP control (adjusted RR 0.89, 95%CI 0.80 to 0.998) compared to usual care. In contrast, withdrawal of beta-blockers was associated with no change in SBP (-4mmHg, 95%CI -10 to 2mmHg) and no difference in SBP control (adjusted RR 1.15, 95%CI 0.96 to 1.37). Similarly, withdrawal of higher dose medications was associated with an increase in SBP but no change in BP control. Withdrawal of lower dose medications was not associated with a difference in SBP or SBP control. There was no association between withdrawal of specific drugs and adverse events. Conclusions: These exploratory data suggest withdrawal of higher dose calcium channel blockers should be avoided if the goal is to maintain BP control. However, low dose beta-blockers may be removed with little impact on blood pressure. Larger studies are needed to confirm these associations.